DETECCIÓN Y ENUMERACIÓN DE BACTERIÓFAGOS F+ ESPECÍFICOS COMO INDICADORES DE ENTEROVIRUS EN EL CHORO (Aulacomya ater) - Miranda C. y Cols., Milagros (2019)
The purpose of this project was to apply the ISO 10705 – 1: 1995 standard method to determine whether the mussel (Aulacomya ater) is a mollusk that is free of viral pathogens at the time it is sold to the public at the Lima fishing ports and some wholesale fresh food markets. As samples we used the mussel viscera and mantle. The methodology employed was the one recommended by the ISO 10705-1:1995 standard, which consisted in the preparation of the master culture and working culture of the strain hosting the Salmonella typhimurium WG49, the detection and enumeration of the strain F+ specific RNA bacteriophages The bacteriophage was detected only in the samples obtained at the Ventanilla fishing port, showing that the concentration in the viscera (6000 to 10000 pfu) was higher than in the mantle (800 to 1400 pfu).